Housewives of Japan - Goldstein-Gidoni, O. author. aut Link
XXV, 273 p. 15 illus.
Keywords: Drawing on a unique ethnographic inquiry, Ofra Goldstein-Gidoni explores the complexities of the relationship between socially and culturally constructed roles bestowed on Japanese women by a variety of state agents, including the market and the media, and the 'real' lives of these women.